2005
DOI: 10.1128/mmbr.69.4.608-634.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analyses of the Bacterial Phosphotransferase System

Abstract: SUMMARY We report analyses of 202 fully sequenced genomes for homologues of known protein constituents of the bacterial phosphoenolpyruvate-dependent phosphotransferase system (PTS). These included 174 bacterial, 19 archaeal, and 9 eukaryotic genomes. Homologues of PTS proteins were not identified in archaea or eukaryotes, showing that the horizontal transfer of genes encoding PTS proteins has not occurred between the three domains of life. Of the 174 bacterial genomes (136 bacterial species)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
253
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(260 citation statements)
references
References 114 publications
(129 reference statements)
5
253
1
1
Order By: Relevance
“…1A, the archetypal PTS system consists of enzyme I (EI), HPr, and enzyme II (EII). Due to their ability to interact with other proteins in the cytoplasm, the set of phosphorylated and nonphosphorylated PTS proteins (more often HPr and EIIA) fulfills regulatory functions as diverse as catabolite repression, chemotaxis, the regulation of cyclic AMP synthesis, or nitrogen assimilation (2)(3)(4). Apart from these PTS components involved in sugar transport, many prokaryotes also have PTS branches that are not involved in carbohydrate traffic.…”
mentioning
confidence: 99%
“…1A, the archetypal PTS system consists of enzyme I (EI), HPr, and enzyme II (EII). Due to their ability to interact with other proteins in the cytoplasm, the set of phosphorylated and nonphosphorylated PTS proteins (more often HPr and EIIA) fulfills regulatory functions as diverse as catabolite repression, chemotaxis, the regulation of cyclic AMP synthesis, or nitrogen assimilation (2)(3)(4). Apart from these PTS components involved in sugar transport, many prokaryotes also have PTS branches that are not involved in carbohydrate traffic.…”
mentioning
confidence: 99%
“…The PTS is a multicomponent system that catalyzes the concomitant phosphorylation and translocation of numerous sugar substrates across the cytoplasmic membrane. This system consists of two general components, enzyme I (EI) and the histidine-containing phosphocarrier protein HPr, which are common to all PTS sugars, along with many sugar-specific components collectively known as enzyme IIs (EIIs) (1,2).…”
mentioning
confidence: 99%
“…After analysis of all 16 completely sequenced haloarchaeal genomes, we found that nine haloarchaea have PTS homologues (Figure 1 PtsI autophosphorylates from PEP and transfers a phosphoryl group to Hpr, and PtsA becomes phosphorylated by the phosphorylated-Hpr and passes the phosphoryl group on to PtsB. PtsC functions as a permease and sugar-specific receptor located in the cell membrane [46]. PtsA, PtsB and PtsC are components of an enzyme complex named enzyme II.…”
Section: Channels and Transportersmentioning
confidence: 99%